1985
DOI: 10.1159/000173955
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy in Primary Aldosteronism: A Long-Term Follow-Up Study

Abstract: The effect of unilateral adrenalectomy in primary aldosteronism was analyzed in 38 patients with unilateral adenoma, 12 cases with idiopathic bilateral hyperplasia and 1 patient suffering from an aldosterone-producing carcinoma. Responses to surgery differed markedly. In all 38 adenoma cases plasma aldosterone dropped to normal levels and remained within normal range during a mean follow-up period of 75 ± 12 months. 23 (61 %) of these patients became normotensive without medication and thus could be classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 20 publications
0
14
1
Order By: Relevance
“…Finally, because patients did not undergo biochemical and hormonal examination at follow-up, we can not completely exclude the recurrence of hyperaldosteronism. However, no patient in our study reported symptoms or signs suggestive of such recurrence, and in general the recurrence of this syndrome is very rare (3,10,11,14,15).…”
Section: Limitationsmentioning
confidence: 59%
“…Finally, because patients did not undergo biochemical and hormonal examination at follow-up, we can not completely exclude the recurrence of hyperaldosteronism. However, no patient in our study reported symptoms or signs suggestive of such recurrence, and in general the recurrence of this syndrome is very rare (3,10,11,14,15).…”
Section: Limitationsmentioning
confidence: 59%
“…From the studies that qualified for this meta‐analysis, two suggested a 0% hypertension resolution rate when unilateral adrenal hyperplasia was the final pathology. This result is highly preliminary as it was derived from only six patients, and therefore has low power, but it may suggest that the magnitude of benefit may be smaller for patients with unilateral IHA pathology . Other papers not included in the meta‐analysis do appear to show clinical benefit to surgical intervention even with diffuse hyperplasia as the pathology .…”
Section: Discussionmentioning
confidence: 87%
“…It is well known that adrenalectomy is the best treatment for adrenocortical adenoma [7,8]. However, our patient had chronic renal failure as a risk factor for surgical treat- ment [15].…”
Section: Discussionmentioning
confidence: 94%
“…Although it has been confirmed that unilateral adrenalectomy is effective in treating aldosterone-producing adrenocortical adenoma [7,8], postoperative hypertension persists in 12-60% of these patients [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%